Countries’ commitments to soil organic carbon in Nationally Determined Contributions - Wiese-Rozanova, Liesl D.; Wollenberg, Eva Karoline; Alcántara Shivapatham, Viridiana; Richards, Meryl B; Shelton, Sadie W; Hönle, Susanna E; Heidecke, Claudia; Madari, Beáta E; Chenu, Claire (Informa UK Limited, 2021)
Soil carbon is the major active pool of terrestrial carbon, and as such, soil organic carbon (SOC) targets, policies and measures will be pivotal to achieving global climate targets. SOC sequestration may reduce the net annual greenhouse gas emissions from Agriculture, Forestry and Other Land Use by between 3% and 71%, while simultaneously supporting various ecosystem services. Accurate SOC accounting and monitoring, however, is constrained by various technical challenges related to indicators, rates of SOC change, measuring the impact of management practices on SOC, and the long-term persistence of sequestered SOC. We assessed countries’ pledges to the Paris Agreement for SOC in agriculture to better understand the level, transparency, and specificity of commitments. Reviewing 184 countries’ initial Nationally Determined Contributions (NDCs), we considered whether SOC was included, what was pledged, the level of ambition promised and the specificity of mitigation targets. Twenty-eight countries referred to SOC in their NDCs, citing quantified or unquantified mitigation targets, national policies or programs, and actions and measures to be implemented in agricultural lands (14), peatlands (6) or wetlands (14). Countries’ reasons for not including SOC in NDCs included the need to prioritize goals of sustainable development and food security above climate mitigation, a lack of incentives for farmers to improve management practices, and the difficulty of accurately monitoring changes in SOC. Including SOC targets in NDCs can improve NDCs’ comprehensiveness and transparency to track and compare policy progress across NDCs; it can also leverage SOC-related climate finance, technical support, and capacity building. Key policy insights: